2020
DOI: 10.1002/macp.201900419
|View full text |Cite
|
Sign up to set email alerts
|

A Dual Stimuli Responsive Supramolecular Gel Provides Insulin Hydrolysis Protection and Redox‐Controlled Release of Actives

Abstract: Two supramolecular hydrogelators containing a central disulfide moiety and terminal carboxylic acid groups are studied. On the one hand, the hydrogels are responsive to a reductive environment, which transforms the disulfide unit to the corresponding thiols. On the other hand, the hydrogels show pH response associated with the presence of carboxylic acid units. Gels are formed at pH below ≈4 while at higher pH values, ionization of the gelators provokes gel disassembly. The properties of the gel are exploited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Supramolecular gels are an important class of materials because of their potential applications such as in catalysis, conservation of arts, light-harvesting materials, conducting materials, ,, sensing, drug delivery, self-drug delivery, tissue engineering, and so forth. Gels are formed from a solution or a suspension containing a solid (gelator) usually by a heating–cooling (to room temperature) process.…”
Section: Introductionmentioning
confidence: 54%
“…Supramolecular gels are an important class of materials because of their potential applications such as in catalysis, conservation of arts, light-harvesting materials, conducting materials, ,, sensing, drug delivery, self-drug delivery, tissue engineering, and so forth. Gels are formed from a solution or a suspension containing a solid (gelator) usually by a heating–cooling (to room temperature) process.…”
Section: Introductionmentioning
confidence: 54%
“…Following our interest in developing molecular gels [25] and nanoparticles [12] sensible to reduction by glutathione, L‐cystine was used as a scaffold to prepare the compound DZC‐Im 2 (Scheme 1). The amine groups of cystine were Z‐protected as described in the literature, [26] and the carboxylic acid units were condensed with histamine (see Scheme S1 and Figures S1–S4 for NMR analysis).…”
Section: Methodsmentioning
confidence: 99%
“…The insulin loaded into the gels prevented its degradation in the pepsin‐containing simulated gastric fluid, where the fibrillar gel network guards insulin and regulates pectin's diffusion to the gel (pectin hydrolyses free insulin instantaneously). Altering acidic pH to neutral pH 7.4 caused gelator solubilization and insulin release [111] . Kumar et al.…”
Section: Supramolecular Gelsmentioning
confidence: 99%
“…Altering acidic pH to neutral pH 7.4 caused gelator solubilization and insulin release. [111] Kumar et al reported enzymatically cleavable and pH-responsive hydrogels based on phenoxy-alkyl maleate-based amphiphiles where the entrapped hydrophobic drug was released via the enzyme-assisted hydrolysis of the ester bond. Moreover, the curcumin-trapped [106] Reproduced with permission from [106] © 2019 American Chemical Society.…”
Section: Othersmentioning
confidence: 99%